Karakteristik Fisikokimia dan Aktifitas Antioksidan Daging Itik yang Dilapisi Ekstrak Propolis Selama Penyimpanan Suhu Ruang - A. Apriantini; S. Adinata; Y. C. Endrawati (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2021)
Duck meat is a perishable food that has a short shelf-life. Therefore, packaging is needed to be used tomaintain duck meat quality during storage, one of the ways to extend shelf-life of duck meat is usingpropolis extract as edible coating which is contained antioxidant substances which can be used to extendduring storage. The aim of this research was to analyze the effect of propolis extract as an edible coatingmaterial on duck meat to maintain the quality and extend shelf-life of duck meat at room temperature.The research was used a completely randomized design (CRD) factorial 4x3 with 3 replications,consisting of 4 propolis concentrations (0.0%, 0.5%, 1.0%, 1.5%) and 3 storage times (0 hours, 6 hoursand 24 hours). Duck meats coated with propolis extracts had a significant effect on the water content andantioxidant activity of duck meat (P < 0.05). The storage time had a significant effect on the pH valueand the cooking loss of duck meat (P <0.05). The addition of propolis extract and storage time had asignificant effect on the pH value, cooking loss and antioxidant activity of duck meat (P <0.05).